Determination of Suitable KCl Polymer Mud Properties for POK Field - Puri Wijayanti; Bayu Satiyawira; Andry Prima; Arinda Ristawati; Foggie Sciorra (Journal of Earth Energy Science, Engineering, and Technology, 2021)
Most oil and gas wellbores are drilled using water based mud (WBM), but this is the case when drilling through non-reactive formations that does not contain swelling shale. In reactive shale formation, KCl Polymer additive should be added to the mud. It will provide a source of potassium ions which will help stabilizing the reactive shale. So that the swelling process is minimized. The basis of the KCL polymer mud system is the polymer used as a wrapper for rock pieces during borehole cleaning process. In the wells in the POK Field, the use of polymer KCL mud is evaluated on trajectories of 17½", 12¼", and 8½ ". The evaluation process uses parameters that aim to find the suitable mud properties that result in the best drilling performance in each trajectory in the POK Field well. The determination of the best drilling performance is based on drilling time. The parameters used in this research are: rate of penetration, trip time, yield point (YP), K+ content, mud weight (MW), viscosity (m), plastic viscosity (PV), and gel strength (GS), mud cake, pH, and additional parameter (excess cement). Based on analysis and investigation, the best drilling performance for trajectory of 17½" occured in POK 1075 well, while the best performance for the trajectories 12¼” and 8½” occured in POK 1058 well. Therefore the KCl polymer mud properties used in these wells can be used as a reference and basis for planning mud systems for the next wells.